Differences between pure desmoplastic melanoma and superficial spreading melanoma in terms of survival, distribution and other clinicopathologic features. (22nd July 2019) - Howard, M.D.; Wee, E.; Wolfe, R.; McLean, C.A.; Kelly, J.W.; Pan, Y.
Abstract: Background: Pure desmoplastic melanoma (pDM) is an uncommon subtype of malignant melanoma with comparative high rates of local recurrence and low rates of sentinel lymph node positivity. The melanoma‐specific survival (MSS) of pDM compared to other melanoma subtypes is unclear, with conflicting reports and lack of multivariable analyses. Objectives: We aimed to describe clinicopathological characteristics of a cohort of patients with pDM and to compare the MSS of pDM with superficial spreading melanoma (SSM). Methods: A prospective cohort study was performed of all primary invasive cutaneous pDM with known tumour location and thickness reviewed at a tertiary referral centre over 21 years. Results: A total of 119 primary cutaneous invasive pDMs from 3570 total invasive cutaneous melanomas were included. Compared to 2272 SSMs, and due largely to their greater average thickness, patients with pDM had worse MSS (unadjusted hazard ratio, HR, 2.56, 95% confidence interval, CI, 1.56–4.22). After adjustment for clinicopathologic factors (including thickness, ulceration, mitotic rate, age and sex), there was evidence that patients with pDM had an improved MSS (adjusted HR, 0.49; 95% CI, 0.28–0.87). Median thickness of head and neck pDM was greater than non‐head and neck pDM ( P  < 0.001). There was reduced univariable MSS in head and neck pDM compared to the rest of the body. Conclusions: Decreased univariable MSS of patients with pDM compared to SSM was explained by the increased frequency of adverse clinicopathologic features at diagnosis, in particular the greater Breslow thickness of pDM. After adjustment, patients with pDM had half the chance of melanoma‐specific death compared to SSM. Head and neck pDM were thicker at diagnosis compared to the rest of the body, which may account for its poorer survival compared to the rest of the body.